Smart safety light / Muhammad Iqmal Hakimi Shukri, Noor Anes Adilla Mohsinin and Nurul Nadia Azni - Shukri, Muhammad Iqmal Hakimi; Mohsinin, Noor Anes Adilla; Azni, Nurul Nadia (2013)
Smart Safety Light is the title of the project Due to accidents at the junction therefore blinking hazard light came as idea. Basically it will display ‘STOP’ when motion detector at the left or right side of the main road detects any movement. The project uses orange LEDs because of its high brightness which suits the aim tobe caution to drivers. Infrared sensor (PIR) is use in order to delects motion. The project takes an inspiration from the original system which is traffic light and some modifications have been made such as displaying ‘STOP’ instead of regular traffic light and will only be display when motion is detected. The system is very effective because it does not need high power consumption or required monitoring of worker except when the maintenance work which is few times a year.The project uses batteries as a main power supply which in 5-12V range.